A Novel Variant of X-Linked Moesin Gene in a Boy With Inflammatory Bowel Disease Like Disease-A Case Report - Fang, Youhong; Luo, Youyou; Liu, Yang; Chen, Jie (Frontiers in Genetics, 2022)
Variants in the MSN gene were recently reported as the cause of a primary immunodeficiency disease called X-linked moesin-associated immunodeficiency (X-MAID). Hitherto, only 10 patients were reported worldwide. Here, we report a boy who presented with recurrent high fever, oral ulcers, abdominal pain, and hematochezia for over two weeks. His serum inflammatory markers were elevated, and colonoscopy showed multiple colon ulcers and terminal ileum ulcers which resemble colitis caused by inflammatory bowel disease. A novel heterozygous variant c.934G>T(p.Glu312Ter) in the MSN gene was identified using whole exome sequencing (WES) and trio analysis. Intestinal ulcers were almost healed after inducing therapy with steroids and maintenance treatment of anti-TNFα. We summarized the genotype and phenotype of reported X-MAID patients and presented the patient’s unique phenotype in this study. This study also expanded the spectrum of MSN mutation-caused immunodeficiency.